Fiber-reinforced plastic and fiber-reinforced plastic molding material

JP2025020581APending Publication Date: 2025-02-13NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023124061
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-13

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、厚み方向(Z軸方向)の熱伝導率が高い繊維強化プラスチック(成形体)を得ることができる。また、本発明の繊維強化プラスチックを得るにあたり用いられる繊維強化プラスチック成形材料は、特殊な織機などが必要ではなく、容易に作製できるために低コストであり、しかも、2次加工での成形も可能な賦形性を有するものであるため、これを硬化させて得られる繊維強化プラスチックは各種の熱伝導部材や、放熱部材として利用することができ、これら以外の用途でも利用可能である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020581000001_ABST
    Figure 2025020581000001_ABST
Patent Text Reader

Abstract

To provide a fiber-reinforced plastic having a high heat conductivity in a thickness direction (Z-axis direction) which is hard to produce by a prior art.SOLUTION: A fiber-reinforced plastic is obtained by laminating and curing a plurality of fiber-reinforced plastic molding materials impregnated with a thermoplastic resin as a matrix resin onto a continuous reinforced fiber substrate, where the thermoplastic resin is an in-situ polymerization-type thermoplastic resin containing a flaky powder, and satisfies the following condition 1 and condition 2. (Condition 1) An average value of minor axes of the flaky powder measured using an SEM in a region where a longitudinal direction perpendicular cross-section of a reinforcing fiber for forming a reinforcing fiber substrate in a cross section of the fiber reinforced plastic is observed is smaller than 0.4 μm. (Condition 2) When a density of the thermoplastic resin containing no flaky powder is ρr, and a density of the reinforcing fiber is ρf, a density of a whole fiber-reinforced plastic is 0.5 ρr+0.5 ρf or more and 0.2 ρr+0.8 ρf or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fiber-reinforced plastic and a fiber-reinforced plastic molding material, and more particularly to a fiber-reinforced plastic that exhibits high thermal conductivity in the thickness direction and a fiber-reinforced plastic molding material for obtaining the same. [Background technology]

[0002] Fiber-reinforced plastics (FRP), which are made by impregnating a matrix resin into a reinforced fiber substrate made of carbon fiber or glass fiber and molding it, are lighter and stronger than metallic materials and are therefore widely used as structural components in a wide range of fields, from the aerospace and aerospace industries to sports and leisure.

[0003] In particular, carbon fiber reinforced plastics (CFRP), which use carbon fiber as the reinforcing fiber, are not only lightweight and strong, but are also used as heat conductive materials, taking advantage of the high thermal conductivity of carbon fiber.

[0004] However, although carbon fibers have good thermal conductivity in the direction of the fiber axis, they have very low thermal conductivity in the direction perpendicular to the fiber axis, and when made into CFRP, this results in large anisotropy in thermal conductivity in the planar and thickness directions. Therefore, methods for forming thermal conduction paths in the thickness direction of CFRP are being investigated.

[0005] For example, Patent Document 1 discloses a reinforcing fiber substrate in which the thermal conductivity in the thickness direction is increased by forming a nonwoven fabric using a needle punch method or a hydroentanglement method, thereby entangling the fibers with each other and promoting the orientation of the fibers in the thickness direction of the substrate, and a highly thermally conductive CFRP using the same; however, this method can only be applied to short fiber substrates.

[0006] Another possible method is to form a heat conduction path by penetrating a rod made of fiber-reinforced resin or fiber-reinforced metal into a laminate made of multiple woven fabrics made of reinforcing fibers, as in Patent Document 2. However, in this method, the inserted rod acts as a spacer during pressure molding, which may cause voids to be generated inside the molded body obtained by molding the laminate, reduce the adhesive strength between layers, and reduce the formability.

[0007] Furthermore, Patent Document 3 discloses a carbon fiber reinforced plastic having a matrix of thermosetting resin containing graphite powder with a particle size of 40 μm or less, with carbon fibers aligned in one direction as a base material, the total of the carbon fibers and graphite powder being 20 to 80 wt%, and the ratio of carbon fibers to graphite powder being 25:75 to 95:5. However, the fiber reinforced plastic of the present invention has a matrix of thermosetting epoxy resin, and secondary shaping processing is not possible. In addition, only the average particle size measured by electron microscopy is described for the graphite powder, and nothing is made clear about impregnation property, thermal conductivity, and the shape and size that allow secondary shaping processing. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent No. 6089447 [Patent Document 2] Jitsuhei No. 3-24356 [Patent Document 3] Japanese Patent Application Publication No. 5-17593 Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide a fiber-reinforced thermoplastic plastic (molded body) having high thermal conductivity in the thickness direction (Z-axis direction), which has been difficult to achieve using conventional methods. [Means for solving the problem]

[0010] In order to solve the above-mentioned problems, the inventors conducted intensive research and discovered that it is possible to increase the thermal conductivity in the thickness direction by forming a molded article from a fiber-reinforced plastic molding material in which a thermosetting resin containing a scale-like powder is impregnated into a continuous reinforcing fiber base material made of a unidirectional material (UD material) in which the reinforcing fibers are aligned in one direction, or a cross material such as a plain weave or twill weave, and thus completed the present invention.

[0011] That is, the gist of the present invention consists of the following (1) to (7). (1) A fiber-reinforced plastic obtained by laminating and curing a plurality of fiber-reinforced plastic molding materials in which a continuous reinforcing fiber substrate is impregnated with a thermoplastic resin as a matrix resin, A fiber-reinforced plastic characterized in that the thermoplastic resin is an in-situ polymerization type thermoplastic resin containing a scaly powder and satisfies the following conditions 1 and 2. (Condition 1) In a cross section of the fiber-reinforced plastic cut in a direction perpendicular to the lamination plane of the fiber-reinforced plastic molding material, the average short diameter of the scaly powder measured using a scanning electron microscope in a region where a cross section perpendicular to the length (axis) direction of the reinforcing fibers constituting the reinforcing fiber base material is observed is less than 0.4 μm. (Condition 2) The density (g / cm) of the thermoplastic resin not containing the scaly powder 3 ) is ρr, and the density of the reinforcing fiber (g / cm 3 ) is ρf, the density of the entire fiber-reinforced plastic (g / cm 3 ) is greater than or equal to 0.5ρr+0.5ρf and less than or equal to 0.2ρr+0.8ρf. (2) The fiber-reinforced plastic according to (1), wherein the reinforcing fiber substrate is made of carbon fiber, and the scale-like powder is graphite powder. (3) A fiber-reinforced plastic according to (1) or (2), wherein the in-situ polymerization type thermoplastic resin is a phenoxy resin. (4) A fiber-reinforced plastic molding material for obtaining the fiber-reinforced plastic according to any one of (1) to (3), wherein the weight-average molecular weight of the matrix resin, an in-situ polymerization type thermoplastic resin, is 300 to 6000. (5) A laminate which is an intermediate product for obtaining the fiber-reinforced plastic according to claim 1 or 2, and which is formed by laminating a plurality of the fiber-reinforced plastic molding materials according to (4), wherein the weight-average molecular weight of the in-situ polymerized thermoplastic resin which is the matrix resin is 10,000 to 30,000. (6) A heat conductive member formed using the fiber-reinforced plastic according to any one of (1) to (3). (7) A heat dissipation member formed using the fiber-reinforced plastic according to any one of (1) to (3). Effect of the Invention

[0012] According to the present invention, it is possible to obtain a fiber-reinforced plastic (molded body) having a high thermal conductivity in the thickness direction (Z-axis direction). In addition, the fiber-reinforced plastic molding material used to obtain the fiber-reinforced plastic of the present invention does not require a special loom or the like, can be easily produced at low cost, and has a shapeability that allows molding in secondary processing, so that the fiber-reinforced plastic obtained by hardening this can be used as various heat-conducting members and heat-dissipating members, and can also be used for other purposes. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is an SEM image showing a region in which a cross section perpendicular to the length (axis) direction of the reinforcing fibers is observed in a cross section of the fiber-reinforced plastic of Example 1 cut in a direction perpendicular to the lamination plane of the fiber-reinforced plastic molding material. [Diagram 2] FIG. 2 is an SEM image showing the same region as in FIG. 1 for the fiber-reinforced plastic according to Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The fiber-reinforced plastic of the present invention, which exhibits high thermal conductivity in the thickness direction (Z-axis direction), is obtained by laminating and curing a fiber-reinforced plastic molding material having a reinforcing fiber substrate made of continuous reinforcing fibers oriented in-plane, a matrix resin of in-situ polymerization type thermoplastic resin, and a scale-like powder, in which the scale-like particles uniformly dispersed in the matrix resin fill the gaps between the reinforcing fibers that form the reinforcing fiber substrate together with the matrix resin, and the scale-like particles form an efficient percolation (thermal conduction path) through the reinforcing fibers, thereby thermally connecting the back and front surfaces of the fiber-reinforced plastic as a thermal conduction path. Here, the scale-like powder refers to a planar body whose ratio of the length other than the thickness is approximately 5 or more.

[0015] The thermally conductive fiber-reinforced plastic of the present invention has a matrix resin that is an in-situ polymerization type thermoplastic resin. This "in-situ polymerization type thermoplastic resin" refers to a reactive precursor composition that is initially in the form of a monomer or oligomer, and that can be rapidly polymerized in situ by heat or the like to be converted into a high molecular weight thermoplastic resin.

[0016] The reinforcing fiber substrates made of continuous fibers impregnated with in-situ polymerized thermoplastic resin as a matrix resin include unidirectional materials (UD materials) in which the reinforcing fibers are aligned in one direction, and cloth materials such as plain weave and twill weave. The reinforcing fibers in these reinforcing fiber substrates include carbon fiber, glass fiber, ceramic inorganic fibers such as alumina fiber, Tyranno fiber, and boron fiber, and organic fibers such as aramid fiber, which are used alone or in combination of two or more types, but from the viewpoint of thermal conductivity, carbon fiber and inorganic fibers are preferred, and carbon fiber is the most preferred. There are two types of carbon fibers: PAN-based carbon fibers and pitch-based carbon fibers. Either of these can be used in the present invention, but from the viewpoint of achieving high thermal conductivity, pitch-based carbon fibers, which have high crystallinity, are preferred.

[0017] The scaly powder in the present invention must be a material with high thermal conductivity in order to function as a heat transfer medium. Materials constituting such particles (powder) include copper, aluminum, alumina, aluminum nitride, boron nitride, diamond, and graphite. Among these, boron nitride and graphite have cleavage and lubricity, and those with high crystallinity can easily obtain scaly particles, and these materials are preferred in that they have high thermal conductivity in the in-plane direction. In particular, graphite with high crystallinity has a thermal conductivity in the in-plane direction of 2000 W / m·K, making it the most preferred heat transfer medium particles of the present invention.

[0018] Here, the most suitable graphite powder as the flake powder may be made from either natural or artificial graphite, but graphite with high purity and high crystallinity is preferred. 3 These have high purity and high crystallinity, and can be crushed to obtain flakes at a relatively low cost, making them more preferable as the raw material for the present invention (the raw material for graphite powder to be mixed with thermoplastic resin to obtain fiber-reinforced plastic molding material). The most preferable is a graphite powder with a true density of 2.2 g / cm. 3 The raw material is natural graphite that satisfies the above requirements. The preferred size of the raw material is an average particle size of 3 μm to 10 μm, as measured by laser diffraction and scattering. In the case of crushed products, if the average particle size is too small, the crystallinity is lost, and the performance as a heat transfer medium is impaired. Also, in order to form a heat conduction path between the reinforcing fibers, a large number of particles must be added, which impairs the moldability of the fiber-reinforced plastic and is therefore not suitable.

[0019] In addition to the scaly powder, graphite powder also exists in earthy and granular powders. These have a smaller specific surface area than the scaly powder, so at first glance they seem to be advantageous for blending, but the graphite crystals of granular graphite are tightly folded, so the particles are difficult to unravel. For this reason, it is difficult for the particles to penetrate between the fibers of the reinforcing fiber substrate, resulting in a resin pool with low thermal conductivity. In addition, earthy graphite has low crystallinity, which is disadvantageous for thermal conductivity, so it is difficult to increase the thermal conductivity of the fiber-reinforced plastic in the thickness direction as in the present invention.

[0020] The scale-like powder dispersed in the matrix resin has an average short diameter of less than 0.4 μm measured (observed) using a scanning electron microscope (SEM) in a region where a cross section perpendicular to the length (axis) direction of the reinforcing fibers forming the reinforcing fiber base material is observed in a cross section of the fiber-reinforced plastic cut in a direction perpendicular to the lamination surface of the fiber-reinforced plastic molding material. If the short diameter of the scale-like powder is 0.4 μm or more, it means that a large number of plate-like crystals are stacked and aggregated, and there are few heat transfer medium particles in the gaps between the reinforcing fibers, so that the dispersion is insufficient, and therefore the formation of percolation is insufficient and thermal conductivity is not expressed. Furthermore, there is a risk that the stacked and aggregated scale-like powder will cause interlayer delamination due to the external force applied during secondary forming, which may become the starting point of internal defects in the fiber-reinforced plastic (molded body). The short diameter of the scale-like powder refers to the thickness of the particles that form the scale-like powder, or more specifically, the plate-like body made of the crystals that form the particles, and is the average value measured after identification using an image of a polished cross section of the fiber-reinforced plastic photographed using an SEM. To facilitate identification, image processing software may be used to convert the image into binary form and perform automatic measurement.

[0021] Regarding the observation surface for observing the minor axis of the scaly powder, if the fiber-reinforced plastic is flat, a cross section perpendicular to the plane (plate surface) and perpendicular to the length direction of the reinforcing fibers that form the reinforcing fiber substrate is used. If the fiber-reinforced plastic is tubular, a cross section perpendicular to the circumscribing surface of the tube and perpendicular to the length direction of the reinforcing fibers is used. If there are multiple directions of the reinforcing fibers, such as in woven fabrics (cloth materials), a cross section is taken so that it is perpendicular to the length direction of the reinforcing fibers in one of the directions, and the minor axis of the scaly powder is evaluated in the region perpendicular to the length direction of the reinforcing fibers. Since the scale-like powder in the fiber reinforced plastic of the present invention is submicron-sized, an instrument capable of identifying the size of submicron-sized particles is used, the observation magnification is at least 5000 times, and the minor axis is measured by measuring 100 or more random particles and taking the average value. If the thickness of one particle varies, the measurement is made at the location of the average thickness.

[0022] In the fiber reinforced plastic of the present invention, the content of the scaly powder is in the range of 10 to 40% by volume relative to the matrix resin. If the graphite powder content is less than 10%, it is difficult to impart high thermal conductivity to the fiber reinforced plastic, while if it exceeds 40%, the amount of matrix resin is reduced and the flowability of the resin is reduced, resulting in a decrease in molding processability, especially secondary processability.

[0023] The fiber reinforced plastic of the present invention has a density (g / cm) of the matrix resin (in-situ polymerized thermoplastic resin) without the scaly powder. 3 ) is the density of the reinforcing fibers forming the reinforcing fiber substrate (g / cm 3 ) is ρf, the density of the whole (whole fiber reinforced plastic) (g / cm 3 ) is 0.5ρr+0.5ρf or more and 0.2ρr+0.8ρf or less. If it is less than 0.5ρr+0.5ρf, the volume ratio (Vf) of the fiber volume and scaly particles (heat transfer medium filler) as fiber reinforced plastics (FRP) is insufficient, or voids are included, resulting in insufficient mechanical strength and high thermal conductivity. Also, if it exceeds 0.2ρr+0.8ρf, the content of reinforcing fibers and scaly particles is too high, resulting in insufficient lubrication and flow of the matrix resin, which significantly reduces secondary processability, making it unsuitable. Therefore, for example, when the reinforcing fibers are carbon fibers and the scaly particles are graphite, in order to obtain the high thermal conductivity that is the effect of the present invention, both need to be highly crystalline and dense, and the density of the graphite particles must exceed 2.1. Therefore, the density of the fiber-reinforced plastic (molded product) of the present invention is set to be 0.5ρr+1.05 or more and 0.2ρr+1.76 or less.

[0024] Examples of in situ polymerization type thermoplastic resins include phenoxy resins, polyamide resins, acrylic resins, and urethane resins. Although these various in situ polymerization type thermoplastic resins can be used as the matrix resin, in situ polymerization type phenoxy resins are preferred.

[0025] In-situ polymerization type phenoxy resin is produced by converting a precursor composition containing a difunctional phenol compound, a difunctional epoxy resin, and a reaction catalyst into a linear polymer, phenoxy resin, in situ in the heating press during the molding process.

[0026] Examples of dihydric phenol compounds used in the production of phenoxy resins are shown below, but are not limited to those shown below as long as they are bifunctional. Bisphenols such as bisphenol A, bisphenol F (all manufactured by Nippon Steel Chemical & Material Co., Ltd.), bisphenol fluorene, biscresol fluorene (all manufactured by Osaka Gas Chemical Co., Ltd.), Bis-E, Bis-Z, BisOC-FL, BisP-AP, BisP-CDE, BisP-HTG, BisP-MIBK, BisP-3MZ, SBOC, Bis25X-F (all manufactured by Honshu Chemical Industry Co., Ltd.), and bisphenol S; benzene diols such as hydroquinone, methyl hydroquinone, dibutyl hydroquinone, resorcin, methyl resorcin, catechol, and methyl catechol; naphthalenediols such as naphthalenediol; and biphenols such as biphenol, dimethyl biphenol, and tetramethyl biphenol. Among these, bisphenol compounds or biphenol compounds are preferred. These dihydric phenol compounds may be used alone or in combination of two or more kinds.

[0027] Examples of bifunctional epoxy resins used in the production of the phenoxy resin include bisphenol type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol acetophenone type epoxy resin, diphenyl sulfide type epoxy resin, diphenyl ether type epoxy resin, and bisphenol fluorene type epoxy resin; biphenol type epoxy resin, diphenyl dicyclopentadiene type epoxy resin, alkylene glycol type epoxy resin, dihydroxynaphthalene type epoxy resin, dihydroxybenzene type epoxy resin, and methyl group-substituted products thereof; and bisphenol type epoxy resin, biphenol type epoxy resin, and methyl group-substituted products thereof are preferred. These difunctional epoxy resins may be used alone or in combination of two or more.

[0028] The reaction catalyst may be any compound having catalytic ability to promote the reaction between an epoxy group and a phenolic hydroxyl group, and examples of such catalysts include alkali metal compounds, organophosphorus compounds, tertiary amines, quaternary ammonium salts, cyclic amines, and imidazoles. Of these, it is preferable to use organophosphorus compounds such as triphenylphosphine (TPP), tri-o-tolylphosphine (TOTP), and tris(p-methoxyphenyl)phosphine (TPAP), and imidazoles such as 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole (TB-Z). These catalysts may be used alone or in combination of two or more kinds.

[0029] Furthermore, since the precursor composition is often heated due to the need for homogeneous liquefaction and viscosity reduction, a reaction retarder may be used to retard the reaction and maintain a low viscosity state. Examples of the reaction retarder include trialkyl borates such as tri-n-butyl borate, tri-n-octyl borate, and tri-n-dodecyl borate, and triaryl borates such as triphenyl borate, and these are used alone or in combination of two or more.

[0030] Therefore, in order to manufacture in-situ polymerization type thermoplastic resins to obtain fiber-reinforced plastic molding materials, first, the raw material compounds and reaction catalysts are mixed using a mixer / kneader such as a planetary mixer, kneader, roll kneader, etc. At this time, in order to optimize the mixed state of the raw materials and reaction catalysts, the raw materials may be mixed after being heated and melted in advance, or a solvent such as cyclohexanone or methyl ethyl ketone up to about 10% by mass may be added.

[0031] Next, after adding a predetermined amount of scaly powder, a solvent such as cyclohexanone or methyl ethyl ketone is gradually added and kneaded to uniformly disperse the graphite powder in the precursor composition. At this time, as a guideline for the amount of solvent added, it is preferable to adjust the solid content (the total amount of the precursor composition and the graphite powder) so that it does not fall below 30%, preferably 40%.

[0032] The impregnation of the precursor composition into the reinforcing fiber substrate is preferably carried out by a wet method. Specifically, the reinforcing fiber substrate is immersed in an impregnation bath filled with the precursor composition in which graphite powder is dispersed, or the precursor composition is directly impregnated into the reinforcing fiber substrate from an impregnation die. In addition, in order to facilitate the impregnation of the precursor resin composition into the reinforcing fiber substrate, for example, heating to about 40°C to 60°C or applying ultrasonic waves may be performed.

[0033] The reinforcing fiber substrate before impregnation is preferably opened. However, since the distance between fibers is generally 10 μm or less, the heat transfer medium particles used must be able to easily penetrate between the fibers of the reinforcing fiber substrate. For this reason, it is preferable that the particles to be mixed into the matrix resin are scaly and have an average particle size of 3 μm or more and 10 μm or less as measured by the laser diffraction / scattering method.

[0034] After the impregnation, excess precursor composition is removed from the reinforcing fiber substrate, and polymerization is continued while volatilizing the solvent in a heating furnace until the weight average molecular weight (Mw) reaches about 300 to 6000, to produce a prepreg (fiber-reinforced plastic molding material).

[0035] If necessary, multiple prepregs can be laminated, vacuum bagged, and heat-treated to form a laminate that serves as an intermediate molding material (intermediate product) also called a preform. In this case, in order to maintain good processability, the Mw of the matrix resin of the laminate is set to a range of 10,000 to 30,000, and preferably to 10,000 to 25,000.

[0036] The molding process uses a conventionally known method such as hot press molding, autoclave molding, and vacuum pressure molding. The distance between the fibers of the reinforcing fiber substrate after molding is preferably narrower than that before impregnation in order to increase the thermal conductivity, so it is preferable to use a pressurizing method and pressurizing conditions that make the thickness of the intermediate molding material smaller than the thickness before molding. Here, in the case of a substrate in which the reinforcing fiber substrate has a mesh-like form such as a woven fabric, the viscosity during impregnation is adjusted so that only the fiber bundles are impregnated with the resin, and the resin spreads into the mesh space during pressurization, thereby reducing the thickness and reducing the distance between the fibers.

[0037] In addition, since the thermally conductive fiber-reinforced plastic of the present invention can be easily subjected to secondary molding processing, it is also possible to consistently produce thermally conductive fiber-reinforced plastic shaped into any three-dimensional shape by combining a heating press machine, pultrusion molding, and roll forming methods.

[0038] INDUSTRIAL APPLICABILITY The thermally conductive fiber-reinforced plastic of the present invention is useful for applications requiring both thermal conductivity and mechanical strength, such as housings for electronic devices such as notebook PCs and tablets, housings and heat sinks for household electrical appliances such as refrigerators, and automotive battery boxes and structures. EXAMPLES

[0039] The present invention will be described in more detail below with reference to examples. The physical properties shown in the examples were measured by the following methods. The parts are by weight.

[0040] (In-situ polymerizable thermoplastic resin) An in-situ polymerized thermoplastic epoxy resin (Nagase ChemteX, base resin: DENATITE XNR6850V, hardener: DENATITE XNH6850V) was used. The density (ρr) of this resin alone after hardening is 1.1 g / cm 3 It was. (Graphite powder) The following graphite powders were used as thermally conductive fillers to be mixed with the in-situ polymerized thermoplastic epoxy resin. Note that JB-3 and UP-5N are flake graphite, and CGB-6R is spherical graphite. JB-3 (made by Nippon Graphite, average particle size (50% cumulative diameter): 3.49 μm, fixed carbon content 99.43%) ·UP-5N (manufactured by Nippon Graphite, average particle size (50% cumulative diameter): 5.88μm, fixed carbon content 99.29%) CGB-6R (Made by Nippon Graphite, average particle size (50% cumulative diameter): 5.13 μm, fixed carbon content 99.28%)

[0041] [Thermal conductivity measurement] The thermal conductivity in the thickness and in-plane directions was measured using the steady thermal gradient method according to ASTM D5470.

[0042] [Density measurement] The density of the resin (ρr) was measured in accordance with JIS K 7112:1999 Measurement method for density and specific gravity of plastics - Non-foamed plastics, Method A, and the density of the reinforcing fiber (ρf) was measured in accordance with JIS R 7603:1999 Test method for carbon fiber density, or the measured value was used.

[0043] [Measurement of minor and major diameters of dispersed particles in a green body] The observation surface was a cross section perpendicular to the plate surface and perpendicular to the length direction of one of the reinforcing fibers that crosses at right angles in the plane. The cross section was smoothed by CP processing (ion milling) to obtain a smooth surface necessary for SEM observation. In this example, a plain weave cloth material was used as the reinforcing fiber, so the cross section was composed of a cross section parallel to the length direction of the reinforcing fiber, a cross section perpendicular to the length direction, and an area of ​​only resin in which graphite particles were dispersed. The shape of the graphite particles was evaluated in an area perpendicular to the length direction of the carbon fiber. The SEM used was a field emission scanning electron microscope (FE-SEM), and evaluation was performed using secondary electron images at a magnification of 5000x. The graphite particles were either scaly or composed of granular particles formed by agglomeration of scaly graphite, and the short and long diameters were measured. The lengths of the short and long diameters varied from place to place within a single particle, but the length at the average point was measured. When measuring the long diameter of a scaly graphite particle that is curved in the longitudinal direction, multiple straight lines were drawn to follow this curve, and the sum of these was taken as the long diameter. Furthermore, when granular particles formed by agglomeration of scaly graphite were formed, the size was measured as a single particle.

[0044] [Mechanical strength measurement] A three-point bending test based on JIS K 7074:1988 Bending test method for carbon fiber reinforced plastics was carried out using a universal testing machine to measure the bending strength and bending modulus.

[0045] [Evaluation of dispersibility] Using the SEM observation sample used to measure the minor and major axes of the dispersed particles in the molded body and an FE-SEM, the dispersed state of the scale particles was observed at a magnification of 1000x and evaluated on a four-level scale of ◎, 〇, △, and × based on the following criteria. (Judgment criteria) ◎: Scale particles are evenly dispersed between the reinforcing fiber monofilaments. ◯: Scale particles are dispersed among the reinforcing fiber monofilaments, but the dispersion state is uneven. Δ: There is large localized unevenness in the dispersion of the scale-like particles. ×: Scale particles are unevenly distributed between the reinforcing fiber substrates.

[0046] Example 1 49.43 parts by weight of graphite particles JB-3 were kneaded with 50.57 parts by weight of the aforementioned in-situ polymerization type thermoplastic epoxy resin (main agent: 46.82 parts by weight and hardener: 3.75 parts by weight), and then methyl ethyl ketone was gradually added to dilute the mixture to prepare a precursor composition varnish with a solid content (total of thermoplastic epoxy resin precursor and graphite particles) concentration of 40 wt%.

[0047] A 200mm x 300mm carbon fiber substrate (PF(S)-YSH60A-75 (open plain weave) manufactured by Nippon Graphite Fiber Co., Ltd.) was immersed in a Teflon (registered trademark) coated stainless steel tray (359mm x 274mm x 60mm) filled with the precursor composition varnish obtained above for 3 minutes while applying ultrasonic treatment, then pulled out and excess resin was removed using a roller, dried at 60°C for 60 minutes in a vacuum oven, and then heat-treated at 160°C for 1 hour in an atmospheric oven to produce a prepreg (fiber reinforced plastic molding material) with a resin weight content (RC) of 30%. The impregnated prepreg had the carbon fiber bundles sufficiently permeated with resin, and although the gaps between the mesh-like carbon fiber bundles were filled, there was still space remaining.

[0048] Four sheets of the obtained prepreg were laminated and processed in a hot press under conditions of a maximum temperature of 160°C and a pressure of 240 MPa to produce a 0.25 mm thick flat plate of thermally conductive fiber-reinforced plastic (molded body). A sample was cut out and its thermal conductivity was measured. The results are shown in Table 1.

[0049] Example 2 A thermally conductive fiber-reinforced plastic was produced in the same manner as in Example 1, except that the graphite particles were changed to UP-5N, and various evaluations were carried out. The results are shown in Table 1.

[0050] Comparative Example 1 A thermally conductive fiber-reinforced plastic was produced in the same manner as in Example 1, except that the graphite particles were changed to CGB-6R, and various evaluations were carried out. The results are shown in Table 1.

[0051] (Reference example) A fiber-reinforced plastic was produced in the same manner as in Example 1, except that the in-situ polymerization type thermoplastic epoxy resin not containing graphite particles was used without diluting it with methyl ethyl ketone, and various evaluations were carried out. The results are shown in Table 1.

[0052] [Table 1]

[0053] The thickness of the obtained molded body was reduced by hot pressing compared to the prepreg state, but the resin carried by the carbon fiber filled the gaps between the single layer fibers, resulting in a dense plate material. From the secondary electron image of the obtained molded body by SEM, it was found that the graphite particles in the molded body obtained in Example 1 and Example 2 were scale-like and uniformly dispersed in the molded body. As can be seen from the SEM image shown in FIG. 1, the graphite particles were uniformly distributed even in the gaps of the reinforcing fibers of 2 μm or less, especially in the molded body obtained in Example 1. On the other hand, in the molded body obtained in Comparative Example 1, as can be seen from the SEM image shown in FIG. 2, the graphite particles were uniformly distributed in places where there were no reinforcing fibers, but in places where the gaps between the reinforcing fibers were small, there were scattered places where no graphite particles were included. These differences in structure are due to the size and shape of the graphite particles used. The short diameter of the graphite particles in the molded bodies obtained in Example 1 and Example 2 was less than 0.4 μm, and it is considered that they easily entered between the fibers during impregnation. In the molded body using granular graphite, the graphite present between the fibers is often of a relatively small particle size or of a flat shape. In other words, it is believed that particles that were relatively small in particle size at the time of impregnation or particles that had been broken down and become smaller were selected and entered between the fibers.

[0054] The thermal conductivity in the thickness direction of the molded body was 5 W / m·K or more for the molded body obtained in Example 1, and about 4 W / m·K for the molded body obtained in Example 2. These values ​​are four times or more thermal conductivity than the approximately 1 W / m·K obtained for the molded body obtained in Example 1, which is a reference example, in which four layers of prepreg were laminated together and prepared without adding graphite to the precursor composition varnish. This is considered to be the effect of the flake-like graphite particles being bound between the carbon fibers, and the fiber spacing being reduced by the heat press, forming a heat conduction path. In fact, as can be seen from FIG. 1, it was observed that one flake-like graphite particle was present close to both of the two adjacent carbon fibers, and that the graphite was bent between the carbon fibers due to the binding of the carbon fibers.

[0055] As described above, the thermal conductivity in the thickness direction of the molded body obtained in Example 1 was 5 W / m K or more. Carbon fiber reinforced plastics are characterized by their high thermal conductivity in the in-plane direction, rigidity, and light weight, and it was demonstrated that the molded body obtained in Example 1 had an in-plane thermal conductivity of 75 W / m K, an in-plane strength of 350 MPa or more, and a Young's modulus of 140 GPa or more, which are high standards even for carbon fiber reinforced plastics, while also ensuring light weight.

[0056] As explained above, it has been found that by making a fiber-reinforced plastic in which scale-like particles with a thickness of less than 0.4 μm are dispersed between the reinforcing fibers, it is possible to provide a fiber-reinforced plastic that has high thermal conductivity in the thickness direction while maintaining the thermal conductivity and rigidity of the fiber-reinforced plastic in the in-plane direction.

Claims

1. A fiber-reinforced plastic obtained by laminating and curing a plurality of fiber-reinforced plastic molding materials in which a continuous reinforcing fiber substrate is impregnated with a thermoplastic resin as a matrix resin, A fiber-reinforced plastic characterized in that the thermoplastic resin is an in-situ polymerization type thermoplastic resin containing a scaly powder and satisfies the following conditions 1 and 2. (Condition 1) In a cross section of the fiber-reinforced plastic cut in a direction perpendicular to the lamination surface of the fiber-reinforced plastic molding material, the average minor axis diameter of the scaly powder measured using a scanning electron microscope in a region where a cross section perpendicular to the length (axis) direction of the reinforcing fibers constituting the reinforcing fiber base material is observed is less than 0.4 μm. (Condition 2) The density (g / cm) of the thermoplastic resin not containing the scaly powder 3 ) is ρr, and the density of the reinforcing fiber (g / cm 3 ) is ρf, the density of the entire fiber reinforced plastic (g / cm 3 ) is 0.5ρr+0.5ρf or more and 0.2ρr+0.8ρf or less.

2. 2. The fiber-reinforced plastic according to claim 1, wherein the reinforcing fiber substrate is made of carbon fiber, and the scaly powder is made of graphite powder.

3. 3. The fiber-reinforced plastic according to claim 1, wherein the in-situ polymerization type thermoplastic resin is a phenoxy resin.

4. A fiber-reinforced plastic molding material for obtaining the fiber-reinforced plastic according to claim 1 or 2, wherein the weight average molecular weight of the in-situ polymerization type thermoplastic resin which is the matrix resin is 300 to 6000.

5. A laminate which is an intermediate product for obtaining the fiber-reinforced plastic according to claim 1 or 2, and which is obtained by laminating a plurality of the fiber-reinforced plastic molding materials according to claim 4, wherein the weight average molecular weight of the in-situ polymerization type thermoplastic resin which is the matrix resin is 10,000 to 30,000.

6. A heat conductive member formed by using the fiber reinforced plastic according to claim 1 or 2.

7. A heat dissipation member formed by using the fiber reinforced plastic according to claim 1 or 2.

Citation Information

Patent Citations

  • Method of preventing polymerization of (METH)acrylic acid ester monomer

    JP1985089447A

  • Mold degassing device

    JP1991024356U

  • Heat-conductive molded article

    JP1993017593A